Regional patterns and controlling factors in plant species composition and diversity in Canadian lowland coastal bogs and laggs - S.A. Howie; H.J. van Meerveld; R.J. Hebda (Mires and Peat, 2016)
Inventories of natural assemblages of plant species are critical when planning ecological restoration of bogs. However, little is known about the regional variation in plant communities at the margins (laggs) of bogs, even though they are an integral element of raised bog ecosystems. Therefore, we investigated the regional patterns in the plant communities of bogs and laggs, and the factors that control them, for thirteen bogs in coastal British Columbia, Canada. Species richness was significantly higher in the bogs and laggs of the cooler, wetter Pacific Oceanic wetland region. Beta Diversity analyses showed that bogs in the Pacific Oceanic wetland region often shared species with their respective laggs, whereas half of the laggs in the warmer, drier Pacific Temperate wetland region had no species in common with the adjacent bogs and were thus more ecologically distinct from the bog. Primary climatic variables, such as mean annual precipitation, mean annual temperature and latitude, as well as climate-influenced variables, such as pH, peat depth, and Na+ concentrations were the main correlates of plant species composition in the studied bogs. Site-specific factors, particularly depth to water table, and fraction of inorganic material in peat samples, were as strongly related to lagg plant communities as climate, while hydrochemistry appeared to have less influence.